Investigation of viability rate and the effects of different breaking treatments of physical dormancy on seed germination of two tree species (Basswood and Black locust) - M. Mollashahi; A.R. Moshki; H. Ravanbakhsh (علوم و فناوری بذر ایران)
Basswood(Tilia begonifolia) and Blacklocust (Robinia pseudoacacia) are two forest trees with seed dormancy due to very hard seed coat. Seeds of two species were collected from Ghorogh nursery in Gorgan province to remove seed coat (breaking seed dormancy) and simplify germniation process and examine the effects of scarification on their germination and viability in 2014.The tetrazolium test was done to measure the seed vitatlity.Then the seed germination rate was tested using hot water (100°C for 1 min. ), H2O2 (1 % for 10 min.), H2SO4 (30 % for 10 min.) and control treatments. The experiment was done in the laboratory of the Faculty of Desert Study (Semnan university). The results of tetrazolium test showed that Tilia begonifolia and Robiniapseudoacacia have 57.25 and 78.30 percent of viability, respectively. The highest rates of seed germination of Tilia begonifolia and Robinia pseudoacacia were observed in H2O2 (%38) and hot water (%66.69) treatments, respectively. As the seeds of Robinia pseudoacacia have higher seed germination than Tilia begonifolia despite of having hard seed coat, it can be concluded that other factors except of hard seed coat can affect seed germination of Tilia begonifolia.  Basswood(Tilia begonifolia) and Blacklocust (Robinia pseudoacacia) are two forest trees with seed dormancy due to very hard seed coat. Seeds of two species were collected from Ghorogh nursery in Gorgan province to remove seed coat (breaking seed dormancy) and simplify germniation process and examine the effects of scarification on their germination and viability in 2014.The tetrazolium test was done to measure the seed vitatlity.Then the seed germination rate was tested using hot water (100°C for 1 min. ), H2O2 (1 % for 10 min.), H2SO4 (30 % for 10 min.) and control treatments. The experiment was done in the laboratory of the Faculty of Desert Study (Semnan university). The results of tetrazolium test showed that Tilia begonifolia and Robiniapseudoacacia have 57.25 and 78.30 percent of viability, respectively. The highest rates of seed germination of Tilia begonifolia and Robinia pseudoacacia were observed in H2O2 (%38) and hot water (%66.69) treatments, respectively. As the seeds of Robinia pseudoacacia have higher seed germination than Tilia begonifolia despite of having hard seed coat, it can be concluded that other factors except of hard seed coat can affect seed germination of Tilia begonifolia.